Notice of an Ancient Cross-bow found under the Moss on the Estate of Auchmeddan, Aberdeenshire, in a Letter to the Secretary - Murray, Alexander (Proceedings of the Society of Antiquaries of Scotland, 1863)
A note explaining how a cross-bow and arrows were unearthed. The arrows were later lost, but the author describes the situation of the finds and argues that the weapons were deposited after the burial of their owner in a cairn nearby. He notes that there are many cairns in this part of Aberdeenshire.